2021
DOI: 10.3389/fcell.2021.746237
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ca2 + in Maturation and Reprogramming of Bovine Oocytes: A System Study of Low-Calcium Model

Abstract: [Ca2+]i is essential for mammalian oocyte maturation and early embryonic development, as those processes are Ca2+ dependent. In the present study, we investigated the effect of [Ca2+]i on in vitro maturation and reprogramming of oocytes in a lower calcium model of oocyte at metaphase II (MII) stage, which was established by adding cell-permeant Ca2+ chelator BAPTA-AM to the maturation medium. Results showed that the extrusion of the first polar body (PB1) was delayed, and oocyte cytoplasmic maturation, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Thus, in this species, calcium rise during oocyte activation seems important for blastocyst development and early cell differentiation during the preimplantation period. This agrees with a recent study that also suggests a crucial role of calcium in the reprogramming of bovine oocytes [ 35 ]. On the contrary, porcine embryos developmental rates were higher and no differences in quality and pluripotent markers were observed.…”
Section: Discussionsupporting
confidence: 94%
“…Thus, in this species, calcium rise during oocyte activation seems important for blastocyst development and early cell differentiation during the preimplantation period. This agrees with a recent study that also suggests a crucial role of calcium in the reprogramming of bovine oocytes [ 35 ]. On the contrary, porcine embryos developmental rates were higher and no differences in quality and pluripotent markers were observed.…”
Section: Discussionsupporting
confidence: 94%
“…The apoptosis inhibitors, HERPUD, DNAJB5, and JMJD6, have already been described. Additional apoptosis inhibitors include: BAG3 [ 39 ], HSP90AA1 [ 40 ], HSPA5 [ 41 ], ID1 [ 42 ] PPP1R10 [ 43 ] and SENP1 [ 44 ], while ZBTB16 [ 38 ] activates apoptosis. Autophagy is a lysosomal based degradation pathway with specific targets that are recycled for cellular maintenance.…”
Section: Resultsmentioning
confidence: 99%
“…ERMCSs are known to function as the multifunctional subcellular structures for the signaling hubs between mitochondria and ER. , Regarding the mitochondria-related results, we observed that DON increased mitochondrial calcium content and caused mitochondrial dysfunction. Given that the ER serves as the primary intracellular calcium storage organelle, we hypothesized that the excessive increase of ERMCSs may lead to a homeostasis imbalance between ER and mitochondria, resulting in a large influx of calcium ions from ER to mitochondria . This, in turn, may lead to mitochondrial calcium ion overload and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the ER serves as the primary intracellular calcium storage organelle, we hypothesized that the excessive increase of ERMCSs may lead to a homeostasis imbalance between ER and mitochondria, resulting in a large influx of calcium ions from ER to mitochondria. 48 This, in turn, may lead to mitochondrial calcium ion overload and dysfunction. Meanwhile, the increased interaction strength of IP3R and VDAC1, known as the calcium channel between mitochondria and ER, further supported our point of view.…”
Section: Discussionmentioning
confidence: 99%